(untitled) (Global Journal of Medical Research, 2021)
Diseases that take place in developing countries could owing to poverty, lack of healthcare infrastructure, restricted access to the hospital. Many developing countries like India growing well economically and extending urbanization in recent years despite this large Indian population lives in poverty. However, risk factors for stroke in urban populations are like other developed nations. Stroke is the third common cause of death due to disease in India. The acute ischemic stroke has to be treated within few hours after the beginning of symptoms; if time goes beyond >4.5 after the onset of symptoms, thrombolytic drugs ineffective not only time, other contraindications also equally contribute to thrombolytic therapy. The use of thrombolytic in contraindication patients would further exaggerate the stroke. The various factors could cause a delay the management of acute ischemic stroke from pre-hospital delay to delay in diagnosis and treatment. An effective strategy is needed to meet the challenges in India.